Academic supervision style as predictor of PhD students' motivation and burnout - Marchuk, L.A. (Psihologičeskaâ nauka i obrazovanie, 2025)
Context and relevance. The relationship of the PhD student and the supervisor acts as one of the crucial factors of motivation, well-being or dropout. Objective. To identify the relationship between academic supervision styles and PhD students' motivation, perseverance, well-being and burnout. Hypothesis. Academic supervision styles will be related to motivation, well-being, perseverance, and burnout directly or inversely depending on whether they support or frustrate basic psychological needs. Methods and materials. The study involved 142 PhD students (M = 28,8, SD = 5,2, 54% female). The theoretical basis of the work was self-determination theory, which allows us to understand the contribution of styles that support or frustrate basic psychological needs to the motivation and outcomes of PhD students' research activities. The study used the Universal Perceived Locus of Causality (UPLOC) and academic burnout scales, the Questionnaires on Academic Supervision Styles (QA2S) and well-being (The PERMA Profiler). Results. The results showed that autonomous and structuring academic supervision styles are the factors of autonomous motivation, whereas controlling and chaotic academic supervision styles are the factors of external motivation and amotivation. The quality of motivation mediates the effect of academic supervision styles on PhD students' perseverance and burnout, specifically cynicism and exhaustion. Autonomous and structuring styles are positively, while chaotic and controlling styles are negatively related to well-being and its aspects. Conclusions. Autonomous and structuring styles are the most favourable for PhD students. Mastering them, as well as reducing the use of unfavourable demotivating styles can become targets of work in the organisation of academic supervisors' professional development. Контекст и актуальность. Отношения аспиранта с научным руководителем выступают одним из решающих факторов мотивации, благополучия или отсева. Цель. Выявить связь стилей научного руководства с мотивацией, настойчивостью, благополучием и выгоранием аспирантов. Гипотеза. Стили научного руководства связаны с мотивацией, благополучием, настойчивостью и выгоранием прямо или обратно в зависимости от того, поддерживают они или фрустрируют базовые психологические потребности. Методы и материалы. В исследовании приняли участие 142 аспиранта (М = 28,8, SD = 5,2, 54% женщины). Теоретической основой работы стала теория самодетерминации, позволяющая понять вклад стилей, поддерживающих или фрустрирующих базовые психологические потребности, в мотивацию и внутренние результаты исследовательской деятельности аспирантов. Использованы шкалы типов мотивационной регуляции (UPLOC) и выгорания, опросники стилей научного руководства (СТИНАРУ) и благополучия (The PERMA Profiler). Результаты. Показано, что факторами автономной мотивации являются автономный и структурирующий стили научного руководства, тогда как факторами экстернальной мотивации и амотивации являются контролирующий и хаотический стили. Качество мотивации опосредует влияние стилей научного руководства на настойчивость и выгорание аспирантов, а именно - цинизм и истощение. Автономный и структурирующий стили положительно, а хаотический и контролирующий отрицательно связаны с общим показателем и отдельными аспектами благополучия. Выводы. Автономный и структурирующий стили наиболее благоприятны для аспирантов, овладение ими, а также снижение использования неблагоприятных демотивирующих стилей могут стать мишенями работы при организации повышения квалификации научных руководителей.